Mortality Among Hardmetal Production Workers: German Historical Cohort Study. Issue 12 (December 2017) - Morfeld, Peter; Groß, Juliane Valérie; Erren, Thomas C.; Noll, Birgit; Yong, Mei; Kennedy, Katrin J.; Esmen, Nurtan A.; Zimmerman, Sarah D.; Buchanich, Jeanine M.; Marsh, Gary M.
Abstract : Objective: The aim of this study was to investigate a cohort in German hardmetal industry, especially relationship between exposures to cobalt, with and without tungsten, and risks of total and cause-specific mortality. Methods: The cohort comprises blue-collar workers at three German plants who were employed in hardmetal processing. Individual cumulative exposures and long-term average concentrations were estimated for cobalt, nickel, tungsten, respirable, and inhalable dust. Standardized mortality ratios (SMRs) were calculated for external comparisons. Time-dependent multivariable Cox models were performed for internal analyses. Results: Elevated SMRs were found for all-cause, heart diseases, and nonmalignant respiratory diseases mortality, but not for lung cancer. Internal analyses did not show increased risks for any endpoints, and no exposure–response relationship was indicated. Conclusions: This study does not provide evidence for elevated lung cancer risks. Methodologic limitations, incomplete ascertainment of death causes in particular, impede conclusions about exposure effects.